(untitled) (Italian Journal of Public Health, 2011)
Background: Waist circumference (WC) is a useful surrogate marker of abdominal adiposity and a risk factor of cardiovascular disease and hypertension. Asians have higher abdominal fat at a lower level of body mass index (BMI). Previous studies showed that WC was the best measure and correlate of abdominal fat and general adiposity, respectively, among the Bengalee people of Eastern India including the present sample. This study aimed to evaluate the clinical usefulness of waist circumference and its appropriate cut-off in identifying obesity and hypertension. Methods: Adult male slum dwellers aged between 18 and 60 years were included in the study. Height, weight, skinfolds, waist circumference, systolic- (SBP) and diastolic blood pressures (DBP) were measured. Body mass index (BMI) and percent body fat (PBF) were also calculated. Obesity was defined as >25% of body fat. Mean (+ SD) and range statistics were used to describe the variables. WC values were divided into four categories, viz. <72cm, 72-79.9cm, 80-84.9cm and ≥ 85.0cm. ANCOVA was performed to observe the differences in mean SBP and, DBP between the WC categories, with age, smoking and alcohol consumption status as covariates. Pearson correlation and multiple linear regressions were employed to examine the relationship of WC with SBP and DBP. Adjusted odds ratios for hypertension by WC categories were obtained through logistic regression analysis. Receiver operating characteristic (ROC) curve analysis revealed the optimal value of WC to identify obesity. Results and conclusions: PBF increased significantly (F = 208.74, p<0.001) from the lowest WC category (10.6%) to the highest one (26.9%). Mean SBP and DBP also increased significantly from the lowest to the highest WC categories. Waist circumference had significant positive effect on both SBP (T=2.559, p<0.01) and DBP (T=3.256, p<0.05) irrespective of age and PBF. WC value >80.9cm could be accepted as the best cut-off point for WC to identify obesity. Participants with a WC of 80-84.9 cm were around three times more likely to have HT(p<0.005), however the likelihood increased to over 5 for those with a WC of > 85.0 cm when compared to lower WC categories. The odds ratio significantly increased for WCs at or above 80cm. Therefore the measurement of WC could be used to identify general obesity and be used as a screening tool for HT risk factors in Bengalee urban slum dwelling men. The WC cut off to define obesity and identifying hypertension was around 81cm